2021
DOI: 10.1080/10803548.2021.1929700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arm position on spatial distribution of upper trapezius muscle activity during simulated car driving

Abstract: The present study aimed to investigate the upper trapezius muscle activity during simulated car driving while adopting three different arm positions. Ten participants were instructed to maintain the following positions: hands on the steering wheel (Hands-On), hands not on the steering wheel (Hands-Off) and hands not on the steering wheel but arms on armrests (Armrests). During the tasks, multi-channel surface electromyography (EMG) was recorded from the upper trapezius muscle with 64 two-dimensionally distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…As a method to estimate motor unit activation or to provide more detailed physiological data, a highdensity surface EMG (HD-SEMG) technique has been developed recently that records surface EMG signals from large areas of muscle using multiple two-dimensionally oriented electrodes 12 . Previous studies reported region-specific muscle activity and muscle fatigue in the upper trapezius muscle 13,14 . Consequently, HD-SEMG could be useful to understand neuromuscular function and/or fatigue in people with FHP.…”
mentioning
confidence: 99%
“…As a method to estimate motor unit activation or to provide more detailed physiological data, a highdensity surface EMG (HD-SEMG) technique has been developed recently that records surface EMG signals from large areas of muscle using multiple two-dimensionally oriented electrodes 12 . Previous studies reported region-specific muscle activity and muscle fatigue in the upper trapezius muscle 13,14 . Consequently, HD-SEMG could be useful to understand neuromuscular function and/or fatigue in people with FHP.…”
mentioning
confidence: 99%